GARBAGE BUSINESS WITH THE 3R METHOD IN AMBON CITY SHARIA BUSINESS PERSPECTIVE - Adam Husain Nusalelu; Mohammad H Holle; Arifin Pellu (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2023)
The waste business in Ambon City has not been carried out optimally, as a result, piles and landfills of waste are still occurring. For this reason, this research aims to determine the waste business process from the perspective of sharia business management.This type of research includes field research with a descriptive qualitative paradigm with a research locus on the Waste Bank in Bumi Lestari Maluku. The results of the study found: First, the waste business conducted by the Bumi Lestari Maluku Garbage Bank is not optimal based on the 3R pattern, namely Reduce, Reuse and Recycle. The Garbage Bank only applies the waste reduction pattern of the three patterns which is only limited to collection, sorting, packaging and sales. The waste bank does not practice reuse and recycling. The 3R pattern must be carried out in an integrated, comprehensive and sustainable manner. Second, the waste business run by the Bumi Lestari Maluku Garbage Bank contains sharia business values because it contains fallah or benefit.